From focus groups to production of a distracted driving video: Using teen input to drive injury prevention programming. (September 2015) - Stewart, Tanya Charyk; Harrington, Jane; Batey, Brandon; Merritt, Neil H.; Parry, Neil G.
Abstract : BACKGROUND: The Impact program is an adolescent, injury prevention program with both school- and hospital-based components aimed at decreasing high-risk behaviors and preventing injury. The objective of this study was to obtain student input on the school-based component of Impact, as part of the program evaluation and redesign process, to ensure that the program content and format were optimal and relevant, addressing injury-related issues important for youth in our region. METHODS: Secondary schools were selected in various geographic regions with students varying in language, religion, and socioeconomic status. A mixed-methods questionnaire was developed and pretested on program content, format, relevance, quality, and effectiveness. Attitude and opinion questions on issues facing teens today were ranked on a 7-point Likert scale. Open-ended, qualitative questions were included in the focus groups, with responses themed. RESULTS: There were 167 respondents in the nine geographically, socioeconomically, and culturally diverse focus groups with a mean age of 16 years, 52% were male, and 69% were in Grade 11. Ninety-three percent of respondents rated the content of Impact as comprehensive (median, 6 of 7, with 7 being very comprehensive), and 29% rated the format a 5 of 7. Impact was rated relevant (89%), addressing issues for teens (median, 6 of 7). Issues suggested to highlight included texting and driving, drugs, partying, self-harm, and abusive relationships. Texting while driving was perceived as a significantly more common (81%) injury issue for adolescents compared with other driving risk factors ( p < 0.001), with one student commenting, "If you don't (text and drive), you either don't have a phone or don't have a driver's license." CONCLUSION: Injury prevention programs must be continually evaluated to ensure they are relevant, addressing issues important for youth, and presented in a format that resonates with the audience. Student focus groups identified motor vehicle collisions and texting as important issues as well as a desire for teens to hear personal stories with a visual element. This provided the information needed to develop the next logical direction for our program, the production of a distracted driving video ("Distracted Driving: Josh's Story, "http://youtu.be/BFPke9gBybc ) to be incorporated into school presentations. LEVEL OF EVIDENCE: Epidemiologic/prognostic study, level III. Abstract : Supplemental digital content is available in the text.